A New Approach of Investment Project Appraisal Under Risk and Uncertainty - Karnavas, Christos (Economics and Business Journal (ECBIS), 2024)
The financial uncertainty in the results of the investment evaluation creates conditions of risk in the decision making of any strategy in the management of the industrial units. The recent crises (economic and pandemic) have only reinforced the need to explicitly introduce the factor of uncertainty in any new investment decision. The aim of the present paper is to develop a methodological approach contributing to the appraisal of an investment project under risk and uncertainty. Methods from statistical - econometrics, probabilistic analysis, numerical simulation methods and financial analysis are used and combined. The stochastic approach is used through the Monte Carlo simulation to appraisal the uncertainty. Finally, the implementation of probabilistic theory combined with the use of decision trees allows to estimate in a more relevant way the factor of uncertainty considering all perspectives.